Integrasi Keilmuan Manajemen dan Keilmuan Psikologi dalam Meningkatkan Efektivitas Kepemimpinan di MIN 1 Gresik - Qomariya Rahma Ayu; Muhammad Thohir; Sahudi Thohir (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to explore the integration of management and psychology to enhance leadership effectiveness at MIN 1 Gresik. In the era of globalization and increasing complexity within educational organizations, leaders’ ability to manage both managerial and psychological aspects has become essential. The research employed a qualitative approach, collecting data through in-depth interviews and direct observations involving the principal, teachers, and administrative staff. The findings indicate that leaders with a strong understanding of emotional intelligence and group dynamics are able to create a positive and productive work environment. Leaders who are sensitive to the psychological needs of team members and capable of managing conflicts effectively contribute significantly to improving motivation and team engagement. Although there is awareness of the importance of psychological aspects in leadership, a substantial gap remains in the practical application of psychological principles within educational settings. Therefore, interpersonal skills training for leaders and staff is necessary to strengthen managerial competence, which can practically serve as a foundation for designing leadership development programs, formulating human resource development policies, enhancing communication, and fostering a supportive work culture oriented toward improving madrasah performance.